Cationic para‐phenyl‐substituted α‐diimine nickel catalyzed ethylene and 4‐methyl‐1‐pentene (co)polymerizations via living/controlled chain‐walking. (27th March 2019) - Zhang, Minghu; Wu, Qitong; Xu, Guoyong; Li, Yougui; Wang, Fuzhou
Abstract : Upon activation with diethylaluminium chloride (Et2 AlCl), a series of phenyl‐substituted α‐ diimine nickel precatalysts conducted 4‐methyl ‐ 1 ‐ pentene (4MP) and ethylene (E) (co)polymerizations via controlled chain‐walking to generate branched amorphous polymers with high molecular weight and narrow molecular weight distribution ( M w / M n < 1.6). The obtained poly(4MP)s were amorphous elastomers with glass transition temperature ( T g ) of −10 −24 °C, which are higher than that of E‐4MP copolymer (− 63.0 °C). At room temperature (25 °C), 4MP polymerization proceeds in a living manner. The microstructures of the produced poly(4MP)s indicated the 2, 1 ‐ and 1, 2 ‐ insertion followed by chain‐walking, the latter being predominant. The NMR analyses of the polymers showed that the obtained poly(4MP) possessed methyl, isobutyl, 2, 4 ‐ dimethylpentyl and 2 ‐ methylhexyl groups, while the isobutyl and 2, 4 ‐ dimethylalkyl branches derived from 4MP were observed in the E‐4MP copolymer. The branch structures and the insertion ‐ type of monomer were depended on the polymerization temperature, and the content of methyl branch increased with an increase in the polymerization temperature. Abstract : 4‐Methyl‐1‐pentene and ethylene were (co)polymerized with cationic para‐phenyl‐substituted α‐diimine nickel catalysts to produce highly branched polyolefins with high molecular weight. The isobutyl and 2, 4‐dimethylalkyl from 4MP were observed in the produced E‐4MP copolymer.